Electrodeposited layered sodium vanadyl phosphate (NaxVOPO4 center dot nH(2)O) as cathode material for aqueous rechargeable zinc metal batteries - Dilwale, Swati; Ghosh, Meena; Vijayakumar, Vidyanand; Kurungot, Sreekumar (Energy & Fuels, 2022)
Aqueous rechargeable zinc metal batteries (ARZMBs) present a safer and cost-effective solution for energy storage in stationary applications. However, a major challenge is the lack of suitable cathode materials simultaneously exhibiting high operating voltage and long cycling stability. Herein, we report the polyanionic sodium-intercalated layered vanadyl phosphate [NaxVOPO4 center dot nH(2)O (NVP)] as a suitable high-voltage and stable cathode for ARZMBs. This work employs a simpler electrochemical route (electrodeposition) for the synthesis of NVP over functionalized carbon fiber substrates and its application as a binder-free cathode in ARZMBs. The electrodeposited NVP possesses a morphology of vertically aligned well-separated nanosheet bundles resembling a flower. When used as the ARZMB cathode, the NVP electrode delivers a specific discharge capacity of 100 mA h g(-1) at 0.033 A g(-1) and high cycling stability (98% retention of the initial capacity over 1100 cycles at 0.333 A g(-1)) in a mild aqueous electrolyte with moderate zinc salt concentration. The observed electrochemical performance of NVP is credited to the synergistic effect of unique nanoflower morphology, the pillaring effect offered by the intercalated Na, and the intimate contact of the active material with the carbon fiber network. These factors are favorable for enhancing the transport of the electrolyte ions and electrons and maintaining the structural stability of the electrode during long-term cycling. The NVP electrode could also deliver appreciable performance (a discharge capacity of 73 mA h g(-) 1 and a current density of 0.033 A g(-1)) in quasi-solidstate ARZMB cells employing PVA/Zn(CF3SO3)(2) gel electrolyte.